Determination of non-isothermal crystallization rate constant of a rotational molding grade LLDPE - Lima,Carlos Alberto Silva de (2015)
The purpose of the present paper was to test the validity of the nonlinear regression method for calculating the non-isothermal crystallization rate constant of the Nakamura's model of a rotational molding grade LLDPE directly from non-isothermal crystallization experiments carried out in a single cell DSC. Cooling rates of 50, 40, 30, 20, 10 and 5 oC/min were used with samples of 3.0 mg under nitrogen atmosphere. Here, good agreement was observed between the experimental relative crystallinity curves and the simulated ones using the calculated parameters by nonlinear regression. It shows that this method can be used to determine the Nakamura's non isothermal rate constant for using in simulation of the cooling phase of rotational molding. In this paper it was used 10-3, 10-4 and 10-14 as the initial crystallinity in the Nakamura's model. However the best average results for all cooling rates was obtained when 10-4 was used. Average spherulitic dimensions of LLDPE studied in this paper did not change significantly with different cooling conditions.